2007
DOI: 10.1089/jam.2006.0531
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Deposition from Nasal Spray Devices Using A Computational Fluid Dynamics Model of The Human Nasal Passages

Abstract: Many studies suggest limited effectiveness of spray devices for nasal drug delivery due primarily to high deposition and clearance at the front of the nose. Here, nasal spray behavior was studied using experimental measurements and a computational fluid dynamics model of the human nasal passages constructed from magnetic resonance imaging scans of a healthy adult male. Eighteen commercially available nasal sprays were analyzed for spray characteristics using laser diffraction, high-speed video, and high-speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 34 publications
11
118
1
3
Order By: Relevance
“…For example, Guo et al (2005) observed that sprays with wider plume angles had increased posterior deposition. Meanwhile, the computational simulations of Kimbell et al (2007) failed to show any effect of plume angle on deposition.…”
Section: In Vitro Deposition Characterization Of Nasal Spraysmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Guo et al (2005) observed that sprays with wider plume angles had increased posterior deposition. Meanwhile, the computational simulations of Kimbell et al (2007) failed to show any effect of plume angle on deposition.…”
Section: In Vitro Deposition Characterization Of Nasal Spraysmentioning
confidence: 99%
“…Despite the high quantitative accuracy and good spatial resolution, these imaging methods require the incorporation of radioactive tracers into the formulation and their execution in a clinical trial. An alternative approach is to use computational fluid dynamics to simulate the particle transport and deposition in an anatomically accurate, three-dimensional computer model of the human nasal passages (Kimbell et al 2007;Inthavong et al 2011). However, the requirement of high computational power and the high complexity of the model construction limit its application in practice.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of nasally administered dose is deposited on the anterior portion reinforced by skin, which is recognized as a poor site for topical as well as for systemic drugs (Duchateau, 1987;Kimbell et al, 2007;Hughes et al, 2008;Kundoor & Dalby, 2010). The deposition of topical steroids at these sites leads to common adverse effects in the form of irritation, bleeding and crusting.…”
Section: Challenges Related To Delivery Devicesmentioning
confidence: 99%
“…Para avaliar a eficiência de deposição das gotículas do spray nasal na cavidade nasal, é importante determinar a distribuição de tamanho de gotículas durante a atomização, pois o tamanho das gotículas está relacionado ao impacto inercial destas na mucosa nasal (INTHAVONG et al, 2014), e quanto menor o tamanho da gotícula, melhor a penetração intra-nasal e maior a deposição na mucosa nasal (KIMBELL et al, 2007), porém gotículas menores que 10µm, podem não ter suficiente impacto inercial (SUMAN, 2013), e atravessar a via nasal se alocando nas vias aéreas (KUNDOOR; DALBY, 2011).…”
Section: Distribuição De Tamanho De Gotículasunclassified
“…Quanto menor o ângulo, maior a penetração intra-nasal, e maior a deposição na mucosa nasal (KIMBELL et al, 2007).…”
Section: Névoa Geométricaunclassified